Subcellular localization analysis of proteins non univocally located to the mitochondria of Trypanosoma brucei - Essmann, Stina (Jihočeská univerzita, 2021)
In this thesis in situ tagging by parasite transfection, followed by Western Blot and immunofluorescence microscopy was performed for the analysis of the endogenous localization of prioritized Trypanosoma brucei proteins. The prioritized non univocally located proteins had TrypTag.org annotations that corresponded or were compatible with tripartite attachment complex (TAC). For the determination of essentiality, RNAi constructs were generated by Gibson assembly molecular cloning.
Subcellular localization analysis of proteins non univocally located to the mitochondria of Trypanosoma brucei
-
Keywords: T. brucei; Western Blot; putative proteins; IFA; localization; mitochondrial; cytoplasmic; T. brucei; Western Blot; putative proteins; IFA; localization; mitochondrial; cytoplasmic